Penggunaan Tanaman Hias untuk Meningkatkan Fasilitas Terapi Anak - Djim, Michael Isnaeni; Demetrius, Yolanda (ComTech: Computer, Mathematics and Engineering Applications, 2014)
In certain circumstances children need to get therapy for supporting their growth and recovering their health. There are at least three types of therapy which are physiotherapy, occupational therapy and speech therapy. The existence of ornamental plants are believed to bring positive effects on therapy for children in condition that the ornamental plants concern positive and negative effects of the therapy activities. This study tried to determine the relationship between the types of therapy activities with the choice of ornamental plants. The result showed that the diversity of colors and scents of different types of plants can improve therapy facilities for children by concerning the therapy characteristics and the compliance with plant characteristics.